Wavelet-based data and solution compression for efficient image reconstruction in fluorescence diffuse optical tomography - Correia, Teresa; Rudge, Timothy; Koch, Maximilian; Ntziachristos, Vasilis; Arridge, Simon (Journal of Biomedical Optics, 2013)
Current fluorescence diffuse optical tomography (fDOT) systems can provide large data sets and, in addition, the unknown parameters to be estimated are so numerous that the sensitivity matrix is too large to store. Alternatively, iterative methods can be used, but they can be extremely slow at converging when dealing with large matrices. A few approaches suitable for the reconstruction of images from very large data sets have been developed. However, they either require explicit construction of the sensitivity matrix, suffer from slow computation times, or can only be applied to restricted geometries. We introduce a method for fast reconstruction in fDOT with large data and solution spaces, which preserves the resolution of the forward operator whilst compressing its representation. The method does not require construction of the full matrix, and thus allows storage and direct inversion of the explicitly constructed compressed system matrix. The method is tested using simulated and experimental data. Results show that the fDOT image reconstruction problem can be effectively compressed without significant loss of information and with the added advantage of reducing image noise. © 2013 Society of Photo-Optical Instrumentation Engineers.
CRIS-Team Scopus Importer:2023-03-08
Keywords: data compression; fluorescence; inverse problems; wavelets